Compensation Analysis of Employee Performance at PT. PLN (Persero) Bukit Asam Power Plant Implementation Unit South Sumatra Power Plant Main Unit - Aprizal*, Aprizal; Widiyanti, Marlina; Yusuf, M.; Hadjri, Muhammad Ichsan (Riwayat: Educational Journal of History and Humanities, 2024)
The purpose of this study is to look into how worker execution in the Southern Sumatra Power Age Unit, PT PLN (Persero) Bukit Asam Power Age Execution Unit, is affected by remuneration. An information assortment approach was used to collect the necessary data for this investigation using a survey that was distributed to all 120 employees who were representatives of the PT PLN (Persero) Bukit Asam Power Age Execution Unit and the Southern Sumatra Power Age Unit. With a relapse value of 0.380, information analysis using simple direct relapse demonstrates that worker execution is significantly impacted by pay. The investigation's findings have a positive effect on worker performance, demonstrating that wage increases coincide with representatives' presence at the PT PLN (Persero) Bukit Asam Execution Unit and the South Sumatra Power Age Unit.